Elastoplastic Model of Sand under Complex Loading - Wan, Z.; Song, C.C.; Gao, W.S. (Проблемы прочности, 2018)
The unified hardening model for overconsolidated clay is extended to the cyclic model considering the stress–strain relationship for sands by adopting the rotational hardening rule. The equations for the normal consolidated line and critical state line are revised in the e-lnp space to describe the breakage behavior of gravel sands under high pressures. The power function is used to define the above equations.